Nitrogen Supply for Cover Crops and Effects on Peanut Grown in Succession under a No-Till System - Crusciol, Carlos Alexandre Costa [UNESP]; Soratto, Rogério Peres [UNESP] (Amer Soc Agronomy, 2009)
In Brazil, as no-till (NT) crop management expands, there is an increased interest in growing peanut (Arachis hypogaea L.) with this system. However, it is not known if the preceding cover crop species, the amount of straw on the soil surface, or the N supplied to the cover crop will affect peanut grown in a NT system. An experiment was conducted on a Typic Haplorthox in Botucatu, São Paulo State, Brazil, during two agricultural years, to evaluate the cover crop dry matter (DM) and nutrient accumulation as affected by N fertilization and peanut nutrition and yield when grown in succession, under a NT system. Treatments included three cover crops {palisadegrass [Brachiaria brizantha (Hochst. ex A. Rich) Stapf], pearl millet [Pennisetum glaucum (L.) R. Brown], and guineagrass [Patticum maximum jacq.]} and two N rates (0 and 60 kg ha(-1)) supplied to the cover crops 50 d after emergence (DAE). Pearl millet showed lower nutrient concentrations in aboveground biomass compared with palisadegrass and guineagrass, but accumulated the largest quantities of DM (14.8 Mg ha(-1)) and macronutrients. Nitrogen application increased N and P concentration in all cover crops, as well as the accumulation of N, Ca, and Mg in pearl millet. Nitrogen-fertilized pearl millet resulted in higher P, Ca, Mg, and S concentrations in peanut leaves grown after. Previous cover crops, even with large straw mulch production (6.0-14.8 Mg ha(-1) of DM), did not influence peanut pod yield (mean 2.3 Mg ha(-1)) in the NT system, nor did N fertilization of the cover crop.